Rational Choice Theory and Charitable Giving - Radovanović, Bojana S. (Sociološki pregled, 2019)
This paper focuses on rational choice theory and its potential to explain prosocial behaviour, precisely charitable giving, defined as monetary contributions to nonprofit organisations. When deciding whether to donate money, rational individuals apply the principle of maximal utility. There are three motives that drive rational individuals to donate: 1) self-interest and enlightened self-interest; 2) pro-social preferences; 3) reciprocity. Although rational choice theory allows for different motives, they are all expressed in terms of utility gained by the decision maker. This paper shows that rational choice theory while appearing to explain “everything”, it does not really explain much. Without the reference to the complexity of people’s motivation and the social and institutional factors that shape our choices, behaviour cannot be understood.